A Review of Combined Training Studies in Older Adults According to a New Categorization of Conventional Interventions - Torre, Marta Maria; Temprado, Jean-Jacques (Frontiers in Aging Neuroscience, 2022)
Physical and cognitive training are effective to attenuate age-related declines of brain and cognition. Accordingly, interest in interventions that combine physical, motor, and cognitive exercises has recently grown. In the present review, we aimed to determine whether and under which conditions combined training could be more effective than separated cognitive and physical training, thanks to a model build around seven interacting constructs (stimuli, settings, targets, markers, outcomes, moderators, and mechanisms), which collectively afford a global picture of the determining factors of combined training. We concluded that the general principles underlying the effectiveness of combined training were still difficult identify, due to the heterogeneity of the available studies. However, our model-based analysis also suggested that, when they are well-designed and well-conducted, combined training interventions are more effective than separated physical and cognitive training to improve brain and cognition in older adults. Also, we identified still not answered questions, which could be addressed in futures studies. Finally, we showed that our model could be also applied to review the literature on training with exergames.